Characterization and determination of mechanical properties of YBCO superconducting thin films with manganese using the TFA-MOD method - Culha, Osman (Materiali in tehnologije, 2013)
The aim of this study is to determine the microstructure, superconducting and mechanical properties of YBasub{2}Cusub{3}Osub{6.56} (YBCO) and YBCO thin films with a manganese (Mn) addition. All the YBCO superconducting films (undoped and Mn-doped) were dip-coated onto (001) SrTiOsub3 (STO) single-crystal substrates with a metalorganic deposition using the trifluoroacetate (TFA-MOD) technique. The phase analysis, microstructure, surface morphologies and critical temperature (Tsubc) of the superconducting thin films were determined with an X-ray diffractometer (XRD), a scanning electron microscope (SEM), an atomic force microscope (AFM) and an inductive Tsubc measurement system. Since the main issue of this study is to determine the mechanical-property variations of the superconducting thin films with/without a Mn addition, the adhesion strength of these films on a STO substrate was tested with a Shimadzu scratch tester. Depending on the Mn addition, the critical forces of pure films increase from 56.23 mN, 58.63 mN and 60.11 mN for pure YBCO, YBCO with 0.05 g and 0.10 g of Mn. Furthermore, Young's modulus and the hardness ofthe undoped and Mn-doped YBCO thin films were measured with a CSM Berkovich nanoindenter using the load-unload sensing analysis under a 0.3 mN applied load.
Keywords: tanke plasti; superprevodniki; sol-gel sinteza; mehanske lastnosti; trdota